Digital Equity and Social Justice in Contemporary Education - Furqon Ahsany; Zakiyyah Al-Fairuzy (PT Mutiara Bustan Ilmu, 2026)
This study investigates the relationship between digital equity and social justice in contemporary education. The study employed a qualitative library research design using a descriptive-analytical approach. Data were collected from books, peer-reviewed journal articles, policy reports, and international publications related to digital equity, educational inequality, and social justice. The collected data were analyzed using thematic content analysis to identify major issues influencing equitable access to education in the digital era. The findings reveal that unequal access to digital technologies, disparities in digital literacy, socioeconomic differences, and variations in educational resources significantly affect students’ participation and academic achievement. Furthermore, teacher competence, institutional support, and educational policies play important roles in promoting inclusive and equitable learning environments. The study concludes that digital equity is a fundamental dimension of social justice in education and requires collaborative efforts from governments, educational institutions, and communities. These findings provide valuable implications for policymakers, educators, and researchers in developing inclusive and sustainable educational systems in the digital age.